Menggugat Syirik Intelektual Bersama Nasr HÃ¢mid AbÃ» Zayd dan Amina Wadud - Basyir, Kunawi (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The article discusses gender issue which has still become a global discourse within 21st century. The discourse will always become an actual issue as it constantly emerges from women and community?s consciousness who find strategic discrepancy and injustice, in regard with the relation between men and women, in which they might lead to relational discrimination, subordination, stereotype, and inequality. The writer, at this point, attempts to bring about comparative analysis between two interpretation paradigms on gender issue promulgated by Nasr Hâmid Abû Zayd and Amina Wadud. Both people share a common academic apprehension when they observe backwardness of the Muslim women in many aspects of life (as a fully human agency) caused by patriarchy tradition, gender injustice, and problem of minority in the Muslim world. This has subsequently caused the two authors to reconstruct methodological paradigm of Quranic exegesis on gender issue in order to generate a just interpretation. They see the importance of having high social consciousness which properly considers women?s existence based on sacred values of humanity. However, this view faces obstacles from other Muslim scholars as they consider Zayd and Wadud heretics and have conducted what so-called ?an intellectual shirk?.